Karakteristik Ultrasonic Pulse Velocity Pada Perkerasan Jalan dengan Menggunakan Filler Bata Tahan Api - Syukuriah, S.; Hustim, M.; Tjaronge, M.W.; Irmawaty, R. (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2024)
Most road pavements in Indonesia use asphalt concrete mixtures. The choice of asphalt concrete is motivated by the fact that the mixture produces a waterproof and durable layer. However, this mixture has weaknesses related to tropical weather conditions. So the mixture is prone to damage, such as potholes and wavy roads. Coupled with heavy transportation equipment passing over the road construction. The development of technology in the field of construction is increasing, one of which is the increasing variety of technology to facilitate road construction work. This research uses the Portable Ultrasonic Nondestructive Digital Indicating Tester (PUNDIT) tool to perform a density analysis process based on the propagation speed of UPV, and this method has been widely used in Indonesia. Ultrasonic Pulse Velocity (UPV) is a tool used to determine material density. This study aims to determine the average ultrasonic wave propagation velocity in pavements before and after soaking using magnesia/converter type refractory brick filler material. This research was conducted at the Structures and Materials Laboratory, Faculty of Engineering, Hasanuddin University. Variations of 5%, 5.5%, 6% asphalt content using AC 60/70 asphalt mixture. Based on this research obtained before soaking: a. The average wave propagation speed of 5%, 5.5%, 6% asphalt content is 3279 m/s, 3473 m/s, 4001 m/s respectively. b The optimal average ultrasonic wave propagation speed value is found at 6% asphalt content, namely 4001 m/s. After soaking: a. The average wave propagation speed of 5%, 5.5%, 6% asphalt content is 3652 m/s, 3667 m/s, 3878 m/s, respectively. b The optimal average ultrasonic wave propagation speed value is found at 6% asphalt content, namely 3878 m/s.